Hubungan Karakteristik dan Partisipasi Petani dalam Program Corporate Farming di Kecamatan Kuwarasan Kabupaten Kebumen - Wijayanto, Destian; Widiyanti, Emi; Rusdiyana, Eksa (AGRITEXTS: Journal of Agricultural Extension, 2025)
Relationship between Characteristics and Farmer Participation in Corporate Farming Program in Kuwarasan Sub-District, Kebumen Regency. The Corporate Farming Program aims to consolidate small landholdings and enhance production efficiency through institutional support, technology, and market access. The success of this program heavily depends on farmer participation, which is influenced by characteristics such as age, education, land size, farming experience, and income. This study aims to examine the characteristics of farmers, their participation levels, and the relationship between them in the Corporate Farming Program in Kuwarasan Sub-district. The research method used is quantitative with a correlational descriptive design. The research sample consists of 30 farmers randomly selected from 92 program participants. Data analysis was conducted using IBM SPSS 27 to identify factors influencing farmer participation. The relationship between farmer characteristics and participation shows that non-formal education has a positive and significant influence on all stages of participation. Farm income also positively influences the planning and utilization stages, while non-farm income tends to reduce participation. Farming experience has a positive influence on the utilization stage. These findings suggest that enhancing non-formal education and farm income can increase farmer participation in the program. Based on the research results, it is recommended that the Agriculture and Food Agency of Kebumen Regency and the Agricultural Extension Center (BPP) of Kuwarasan enhance land consolidation and mentoring strategies to maximize farmer participation. Farmers are also encouraged to be more active in farmer group activities, while successful farmer groups can organize workshops or exhibitions to attract other farmers. Local governments are expected to facilitate access to services for farmer groups. Thus, the Corporate Farming Program can be more effective in empowering smallholder farmers and improving agricultural productivity in Kuwarasan Sub-district.